Training of Adding Turmeric and Curcuma as Food Additives for Laying Hens - Ika Nur Fitriani; Kholidah Kholidah; Mutista Hafshah; Achmad Hasmy Hashona (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
The use of bioactive plants to replace antibiotics is now widely used. The program's purpose is to provide a solution for natural feed additives to laying hens in Ngaliyan as a substitute for Antibiotics Growth Promotor (AGP), which is prohibited by the government, and provide knowledge to farmers about the use of medicinal plants to improve the productivity of livestock. The target was laying hens farmers in Ngaliyan. The problem was chicken feed is made without AGP and egg prices fell while feed prices had risen. The solution offered to the partner was adding food additives from turmeric and Curcuma. Turmeric and Curcuma will improve immunity to increase livestock productivity, feed efficiency, and egg quality. Based on this reason, we conducted community services for laying hens farmers in Ngaliyan. Community service activities were carried out using the PAR method for two months through socialization, training, assistance in providing additional natural feed, and evaluation. Giving turmeric and Curcuma flour can improve the quality of eggs. The result of the community service showed an understanding of partners to formulate and produce feed additives in raising laying hens was improved. In addition, farmers were able to formulate and produce herbal feed based on requirements.